Survival and Recurrence in Vitreoretinal Lymphoma Simulating Uveitis at Presentation: The Possible Role of Combined Chemotherapy. (17th November 2022) - Gozzi, Fabrizio; Aldigeri, Raffaella; Mastrofilippo, Valentina; De Simone, Luca; Bolletta, Elena; Marzano, Jacopo; Iannetta, Danilo; Coassin, Marco; Ilariucci, Fiorella; Ferrari, Angela; Luminari, Stefano; Merli, Francesco; et al.
ABSTRACT: Purpose: To investigate the role of combined systemic and local chemotherapy in improving the survival of patients with vitreoretinal lymphoma (VRL). Methods: Patients with VRL consecutively seen from 2006 to 2020 were retrospectively reviewed; data on the presence and time of central nervous system (CNS) involvement and treatment regimen (systemic, local or combined chemotherapy) were collected. Overall survival (OS) and progression-free survival (PFS) were calculated for each group. Results: Forty-three eyes of 22 subjects with histology-proven VRL were included. Mean time of survival was 64.8 months (SE±10.8). Twelve patients (57%) presented CNS involvement, which was significantly associated with progression (r = 0.48, P = .03) and death (r = 0.56, P = .009). The isolated primary VRL group had a 5-year OS of 80%. Combined systemic and local chemotherapy reduced the risk of death by 82% (hazard ratio 0.18[0.04– 0.85]) in the entire cohort. Conclusion: Combined systemic and local chemotherapy significantly improved OS but not PFS of patients affected by VRL.